CEO Power and Tax Avoidance in Malaysia: The Moderating Effect of Board Gender Diversity - Hooy Guat-Khim; Phua Lian-Kee (Asian Academy of Management Journal of Accounting and Finance, 2024)
This study examines the relationship between chief executive officer (CEO) power and tax avoidance and the moderating effects of board gender diversity on this relationship. Based on companies listed on the Main Market of Bursa Malaysia from 2009 to 2019, it is found that CEO power is positively associated with tax avoidance. This suggests that CEOs with more dimensions of power are more competent in reducing the firm’s tax burden. Further tests show that this positive relationship is strengthened by board gender diversity. This implies that CEO competence in tax avoidance increases as the proportion of female directors on the board increases.